Comparative study of single precision floating point division using different computational algorithms - Naginder Singh; Kapil Parihar (Institute of Advanced Engineering and Science, 2023)
This paper presents different computational algorithms to implement single precision floating point division on field programmable gate arrays (FPGA). Fast division computation algorithms can apply to all division cases by which an efficient result will be obtained in terms of delay time and power consumption. 24-bit Vedic multiplication (Urdhva-Triyakbhyam-sutra) technique enhances the computational speed of the mantissa module and this module is used to design a 32-bit floating point multiplier which is the crucial feature of this proposed design, which yields a higher computational speed and reduced delay time. The proposed design of floating-point divider using fast computational algorithms synthesized using Verilog hardware description language has a 32-bit floating point multiplier module unit and a 32-bit floating point subtractor module unit. Xilinx Spartan 6 SP605 evaluation platform is used to verify this proposed design on FPGA. Synthesis results provide the device utilization and propagation delay parameters for the proposed design and a comparative study is done with previous work. Input to the divider is provided in IEEE 754 32-bit formats.